2013
DOI: 10.1515/hf-2013-0045
|View full text |Cite
|
Sign up to set email alerts
|

Selective purification of bleached spruce TMP process water by induced air flotation (IAF)

Abstract: The environmentally benign closure of water systems in paper mills leads to the problem of accumulation of dissolved and colloidal wood substances (DCS) in process water. Notably, pitch affects the pulp and paper production negatively and increases the demand for additional treatment of the process water. In the present article, the purification of thermomechanical pulping process water from the alkaline peroxide bleaching stage has been investigated, with the induced air flotation (IAF) in focus. The followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Accumulation of dissolved and colloidal wood substances in the process water upon recirculation is known to cause impairments to the paper quality. 2 Instead of discarding this side stream to waste water treatment plants, as it is currently the case, its valorisation for renewable materials or active biomolecules production can result in significant improvement of TMP plants profitability while greatly reducing the amount of generated wastes. 3 Although the concentration of wood constituents in the process water is low (in the range of 1g.L -1 Membrane filtration processes have proved their suitability as an energy-efficient separation technique for the recovery of substances at really low concentration.…”
Section: Complexes Towards Zero-waste Biorefineriesmentioning
confidence: 99%
“…Accumulation of dissolved and colloidal wood substances in the process water upon recirculation is known to cause impairments to the paper quality. 2 Instead of discarding this side stream to waste water treatment plants, as it is currently the case, its valorisation for renewable materials or active biomolecules production can result in significant improvement of TMP plants profitability while greatly reducing the amount of generated wastes. 3 Although the concentration of wood constituents in the process water is low (in the range of 1g.L -1 Membrane filtration processes have proved their suitability as an energy-efficient separation technique for the recovery of substances at really low concentration.…”
Section: Complexes Towards Zero-waste Biorefineriesmentioning
confidence: 99%
“…Traditionally, the pitch problem is controlled by seasoning wood, although new approaches are constantly appearing. 44,45 The extraction of the wood would probably reduce and/or avoid the "pitch problem". However, other uses such as wood composites would also be suitable.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Another option, especially if the water contains chlorides or other species incompatible with a chemical recovery plant, is to send the filtrate from pulp washing to wastewater treatment. Alternatively, the surface-active compounds and hydrophobic matter can be separated by dissolved air or induced air flotation (Negro et al 2005;Korpela 2006;Tanase-Opedal et al 2011a,b;Strand et al 2012;Zasadowski et al 2013;Singh et al 2016). Zasadowski et al (2013) showed that induced air flotation, carried out under optimized conditions of pH and other variables, could remove 90% of the pitch-forming matter and up to 70% of pectic acids, which contribute to a high cationic demand of the furnish.…”
Section: Deresinationmentioning
confidence: 99%
“…Alternatively, the surface-active compounds and hydrophobic matter can be separated by dissolved air or induced air flotation (Negro et al 2005;Korpela 2006;Tanase-Opedal et al 2011a,b;Strand et al 2012;Zasadowski et al 2013;Singh et al 2016). Zasadowski et al (2013) showed that induced air flotation, carried out under optimized conditions of pH and other variables, could remove 90% of the pitch-forming matter and up to 70% of pectic acids, which contribute to a high cationic demand of the furnish. Reduced pH conditions were found to be favorable for such separations (Strand et al 2012;Zasadowski et al 2013).…”
Section: Deresinationmentioning
confidence: 99%
See 1 more Smart Citation